CLASSROOM INTERACTION BETWEEN TEACHER AND YOUNG LEARNERS IN ENGLISH AS FOREIGN LANGUAGE CLASSROOM - Risa Puspitaningrum, - (2023)
Since English becomes a compulsory subject in primary school, classroom interaction becomes crucial in English as Foreign Language (EFL) classrooms in order to enhance learners' communication skills, especially in English Young Learners (EYL) context. The result of classroom interaction analysis between English teacher and learners is beneficial to support the importance of learning English in Indonesian primary school curriculum. Thus, this study was employed as a depiction to portray classroom interaction between teacher and young learners in a private primary school using Flanders Interaction Analysis Categories System (FIACS). The case study approach is used to investigate the interaction between an English teacher and fifth graders through classroom observation and interview. The result yielded that all categories of teacher talk, student talk, and silence appeared during the learning process. However, teacher talk dominated the classroom interaction with the amount of 59.91% in all four meetings. In addition, the category of giving direction became the most dominant category of teacher talk and student talk-response became the most dominant category of student talk. It is in line with the result of matrix analysis which showed that giving direction and asking questions are used to create the pattern of teaching behavior which included ice breaking, watching learning video, small-group discussion, and ended with individual assignment. To conclude, the balance of teacher talk and student talk is suggested by giving direction and asking questions to obtain learner's responses as attempts of enhancing learner's engagement in the learning process.